The Role of Facebook Social Media on Goat Sales Levels in Sunju Village - Oktavianus; Ira Nuriya Santi; Zakiyah Zahara (PT. Global World Scientific, 2024)
This study aims to explore the role of social media Facebook in increasing goat sales in Sunju Village. Based on the results of interviews with goat farmers who have participated in training, it was found that the use of Facebook as a marketing platform effectively increases demand for their products. The training provided includes how to utilize Facebook features, such as Marketplace and creating attractive promotional content, which has been proven to expand the market and increase sales. In addition, the use of social media allows farmers to reach consumers without having to spend high transportation costs. The results of this study indicate that by using Facebook effectively, goat farmers can expand their market, increase product visibility, and increase their income. Therefore, it is important for farmers to be given training and assistance in utilizing social media for marketing. With the right understanding and skills, goat farmers can optimize the potential of social media and create new opportunities in their businesses. This study underlines the importance of education and training in developing the capacity of livestock businesses, as well as its contribution to the village economy.